(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, who bestowed favor upon humanity by sending the Seal of the Prophets, and prayers and peace be upon Muhammad bin Abdullah, the envoy as a mercy to the worlds, and upon all his companions.The historical codification of Andalusia had a great resonance and great importance in teaching the Islamic religion among the peoples of the region. After the end of the stage of the Islamic conquest in Andalusia and during the historical period, which is the eight centuries, there are many aspects that need research and scrutiny so that the researcher can reach the historical facts in his writing on this subject, but I worked hard to give the subject its due by searching for sources that fulfill the purpose The research, by shedding light on the role of Arabs and Muslims in writing history in Muslim Spain, i.e. (Andalusia), which was one of the pillars of the Arab-Islamic world in the Middle Ages. In view of the comprehensiveness and ramifications of the subject, I limited myself in writing my research to the emergence and development of historical writing and its first pioneers. Then, after that, I focused on one advanced stage in which the Al-Razi family emerged, and what this family played a great role in serving Arab-Islamic history in Spain and the role of this history in serving human civilization in general.